1986
DOI: 10.1007/bf02555015
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and treatment of acute appendicitis in the aged

Abstract: Since the turn of the century, the elderly population, particularly those over the age of 80, has been increasing steadily. Consequently, the surgeon will be confronted frequently with the diagnostic challenge of acute appendicitis in this population. Over the past ten years, 13 patients over the age of 80 were treated for acute appendicitis at the St. Lukes-Roosevelt Hospital Center. The mean duration of symptoms was 2.4 days; all patients complained of abdominal pain, with 72 percent of patients having right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 7 publications
2
16
0
4
Order By: Relevance
“…Delay in presentation was found by many authors to be the reason behind the higher rate of perforation seen in the elderly population [2,3,6,7,13,15-17]. Our study showed that perforation rate correlated well with delayed presentation (pre-hospital delay) but did not correlate with the in-hospital delay.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Delay in presentation was found by many authors to be the reason behind the higher rate of perforation seen in the elderly population [2,3,6,7,13,15-17]. Our study showed that perforation rate correlated well with delayed presentation (pre-hospital delay) but did not correlate with the in-hospital delay.…”
Section: Discussionsupporting
confidence: 44%
“…As compared to younger age group, elderly patients have more underlying diseases and sluggish bodily physiological reactions resulting in a higher rate of morbidity and mortality [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…2,3,17,26 In the present study, the mean age was around 30 years. This was similar to other studies.…”
Section: Discussionmentioning
confidence: 49%
“…Once admitted, a considerable further delay of operative treatment is also noted. Several studies confirm that postadmission delay is a major contributor to unfavorable outcomes in older patients with appendicitis [5,6,7,8,12,15,16,17,18].…”
Section: Discussionmentioning
confidence: 96%